Emission of cyanobacterial volatile organic compounds and their roles in blooms - Zuo, Zhaojiang (Frontiers in Microbiology, 2023)
Cyanobacteria are photosynthetic prokaryotes and one of dominant species in eutrophicated waters, which easily burst blooms in summer with high irradiance and temperature conditions. In response to high irradiance, high temperature and nutrient conditions, cyanobacteria release abundant of volatile organic compounds (VOCs) by up-regulating related gene expression and oxidatively degrading β-carotene. These VOCs not only increase offensive odor in waters, but also transfer allelopathic signals to algae and aquatic plants, resulting in cyanobacteria dominating eutrophicated waters. Among these VOCs, β-cyclocitral, α-ionone, β-ionone, limonene, longifolene and eucalyptol have been identified as the main allelopathic agents, which even directly kill algae by inducing programmed cell death (PCD). The VOCs released from cyanobacteria, especially the ruptured cells, exhibit repelling effects on the herbivores, which is beneficial to survival of the population. Cyanobacterial VOCs might transfer aggregating information among homogeneous species, so the acceptors initiate aggregation to resist the coming stresses. It can be speculated that the adverse conditions can promote VOC emission from cyanobacteria, which play important roles in cyanobacteria dominating eutrophicated waters and even bursting blooms.